Teaterproduksjon ti produksjonsestetiske innganger - Aune, Vigdis; Haagensen, Cecilie (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
This anthology presents research in theatre studies developed by a group of colleagues at the Department of Arts and Media Studies at the Norwegian University of Science and Technology. The research is conducted through arts-based research and practical-theoretical teaching at the department. Theatre production is a central arts-and knowledge-creating field of work for students and teachers in theatre studies. The work is characterized by a dynamic relationship between body, text, visuality and sound, media methods and techniques and the relationship between professionals and students. Theatre production is a complex learning arena; it is both multimodal and developed in dynamic movements between experience, dissemination, response and reflection. There is a need for a rich range of strategies, methods and techniques. The anthology presents ten different inputs to theatre production. Laboratory with experimental methods is the framework for articles on scenography, sound, the body and text of the actor. Production processes setting the creative and reflective student in the centre is the frame for articles on dramaturgy, text processing, production phases and target group- oriented work. The role and function of the university teacher in supervision and assessment is themed in two closing articles. In discussing the different aesthetical inputs to theatre production the authors use examples, images and audio material.